Effects of Rosemary (Rosmarinus officinalis L.), Onion (Allium cepa L.) Extracts as Feed Additive on Layers Performance, Hematological and Blood Biochemical Parameters of White Leghorn - Bekele Alemu , Seyoum; Girma Abebe, Meseret; Kebede Senbeta, Ewonetu (Journal of Poultry Sciences and Avian Diseases, 2025)
The study was conducted to evaluate the effects of rosemary and onion extracts on leave performances and some hematological and serum biochemical parameters of White Leghorn layers at Haramaya University Poultry Farm. One hundred twenty (120) White Leghorn layers at thirty-two weeks of age were randomly allocated to four treatments, each replicated three times with ten layers and one cock per replication and managed on a deep litter system for 70 days. The treatments were T1 (control group without any addition of feed additives), T2 (water with 4 milliliters of onion extract), T3 (water with 4 milliliters of rosemary extract), and T4 (water with 4 milliliters of onion and rosemary extract mixture). Body weight was taken at the beginning and end of the experiment to determine body weight change. Feed intake was determined as the difference between the feed offered and refused divided by the total number of layers in the replication. Data were subjected to be analyzed by SAS software version 9.4 (SAS, 2019), and the significance in treatment mean was determined by the least significance difference (LSD) for all parameters considered. The daily feed intake of chickens in T2 (97.59±0.72g) was significantly (P < 0.01) higher than the feed intake of chickens in T1, T3, and T4. There was no significant difference in PCV percentage, but there is a significant (P